2022
DOI: 10.1111/odi.14351
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of hsa‐circ‐0107593 promotes osteogenic differentiation of hADSCs via miR‐20a‐5p/SMAD6 signaling

Abstract: ObjectivesIncreasing evidence indicated circRNAs were involved in stem cells osteogenesis differentiation. Herein, we aimed to clarify the role of hsa‐circ‐0107593 during the osteogenesis process of human adipose‐derived stem cells (hADSCs) and the underlying mechanisms.MethodsThe ring structure of hsa‐circ‐0107593 was confirmed using RNase R treatment and Sanger sequencing. Nucleoplasmic separation and fluorescence in situ hybridization detected hsa‐circ‐0107593 distribution. Lentivirus and siRNA were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Studies have shown that downregulation of hsa-circ-0107593 promotes the osteogenic differentiation of hADSCs through miR-20a-5p/SMAD6 signaling (51). Atorvastatin may be involved in lipid-lowering therapy by downregulating microRNA-20a-5p (52).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that downregulation of hsa-circ-0107593 promotes the osteogenic differentiation of hADSCs through miR-20a-5p/SMAD6 signaling (51). Atorvastatin may be involved in lipid-lowering therapy by downregulating microRNA-20a-5p (52).…”
Section: Discussionmentioning
confidence: 99%
“…Regulates the switch between osteogenesis and adipogenesis by sponging miR-338-3p [57] circ-3626 Promotes osteogenesis by via miR-338-3p/Runx2 axis [7] Circ-FK501 Promotes osteogenic differentiation via microRNA-205-5p/RUNX2 axis [58] hsa-circ-0107593 Inhibits osteogenic differentiation via miR-20a-5p/SMAD6 signaling [59] Circ_0006873 Inhibits osteogenic differentiation via miR-20a-/SMURF2 signaling [60] Circ_0114581 Promotes osteogenic differentiation via the MiR-155-5p/HNRNPA3 axis [61] Circ_0001825 Promotes osteogenesis via miR-1270/SMAD5 axis [62] Circ_0036872 Promotes osteogenesis via miR-143-3p/IGF2 axis [63] CircZNF367 Inhibits osteogenic differentiation via reducing HuR-mediated mRNA stability of LRP5 [64] Circ_C4orf36 Promotes osteogenesis by regulating VEGFA [65] Circ-Sirt1 Promotes osteogenesis by activating Sirt1 and Wnt/β-catenin pathway [66] CircRNAs also play roles in maintaining bone homeostasis by regulating bone metabolism and the remodeling processes. For example, circRNA_ circ_0006859 was found to inhibit osteogenesis and promote adipogenesis in human in human bone marrow mesenchymal stem cells by targeting the signaling miR-431-5p/Rho-associated protein kinase 1 (ROCK1) [67] and circRNA-CDR1 promotes adipogenesis and inhibits osteogenic differentiation in osteonecrosis of the femoral head [68].…”
Section: Circ-dab1mentioning
confidence: 99%
“…MiR-20a, a mechanosensitive miRNA was found to enhance fluid shear stress-mediated osteogenic differentiation of rat BMSCs via the activation of BMP-2 signalling pathway by targeting Bambi and Smad6 [ 270 ]. In addition, silencing of hsa-circ-0107593 was found to upregulate miR-20a-5p expression, in which stimulated osteogenic differentiation of human ADSCs through targeting of Smad6 [ 271 ].…”
Section: Microrna Regulation Of the Smad Cascadesmentioning
confidence: 99%